Characterization of NGF, trkANGFR, and p75NTR in Retina of Mice Lacking Reelin Glycoprotein - Bijorn Omar Balzamino; Filippo Biamonte; Graziana Esposito; Ramona Marino; Francesca Fanelli; Flavio Keller; Alessandra Micera (International Journal of Cell Biology)
Both Reelin and Nerve Growth Factor (NGF) exert crucial roles in retinal development. Retinogenesis is severely impaired in E-reeler mice, a model of Reelin deficiency showing specific Green Fluorescent Protein expression in Rod Bipolar Cells (RBCs). Since no data are available on Reelin and NGF cross-talk, NGF and trkANGFR/ p75NTR expression was investigated in retinas from E-reeler versus control mice, by confocal microscopy, Western blotting, and real time PCR analysis. A scattered increase of NGF protein was observed in the Ganglion Cell Layer and more pronounced in the Inner Nuclear Layer (INL). A selective increase of p75NTR was detected in most of RBCs and in other cell subtypes of INL. On the contrary, a slight trend towards a decrease was detected for trkANGFR, albeit not significant. Confocal data were validated by Western blot and real time PCR. Finally, the decreased trkANGFR/ p75NTR ratio, representative of p75NTR increase, significantly correlated with E-reeler versus E-control. These data indicate that NGF-trkANGFR/ p75NTR is affected in E-reeler retina and that p75NTR might represent the main NGF receptor involved in the process. This first NGF-trkANGFR/ p75NTR characterization suggests that E-reeler might be suitable for exploring Reelin-NGF cross-talk, representing an additional information source in those pathologies characterized by retinal degeneration.